Kandungan Lipid Beberapa Jenis Sianobakteria Laut Sebagai Bahan Sumber Penghasil Biodiesel - Sobari, Rifana; Susanto, Antonius Budi; Susilaningsih, Dwi; Rahma, Delicia Yunita (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Microalgae are an organism that contains of chlorophyll, so it can make the process of photosynthesis. The process of photosynthesis is the content of lipid producing microalgae as a potential feedstock biodiesel producer. Microalgae have the ability to generate huge natural oils (lipids). The aim of this study is to investigate the characteristic of morfologi and growth of microalgae marine cyanobacteria of Indonesian water that have the most lipid content, so it can be used as raw material for biodiesel. The research was carried out in September 2011 - February 2012. The implementation of the research carried out at the Laboratory of Bioprocess, Biotechnology Research Center Indonesian Institute of Sciences (LIPI) Cibinong, Bogor. Result microalga identification done using Nikon SE light microskop with identification book whareas lipid content ekstraction microalga done with Bligh and Dyer method (1959). The results showed that the microalgae sianobacteria had base of morfologi characteristic is the type of Oscillatoria sp.1, Oscillatoria sp.2, Nostoc sp., Synecococcus sp. and Lyngbya sp.. The highges growth OD marine cyanobacteria is type of Nostoc sp. and the lowest growth is type of Oscillatoria sp.2. Lipid content on Oscillatoria sp.1 4,2 mg/25 ml, Oscillatoria sp.2 3,7 mg/ 25 ml, Nostoc sp. 3,3 mg/25 ml, Synecococcus sp. 4 mg/25 ml and Lyngbya sp. 7,1 mg/25 ml.